Fibreoptic endoscopic palliative intubation of inoperable oesophagogastric neoplasms. Issue 6056 (29th January 1977) - Atkinson, M; Ferguson, R
Abstract : Palliative intubation for inoperable malignant strictures at the cardia was done on 16 occasions in 13 patients using fiberoptic endoscopy. Preliminary dilatation was performed, and the Celestin tube was mounted on an introducer and passed over a guide wire inserted with a fiberoptic endoscope. Only one death resulted from the procedure and all the 12 patients who left hospital were swallowing satisfactorily on discharge. The method provided a simple and relatively safe means of relieving dysphagia and improving nutrition.